ASUHAN KEPERAWATAN PADA PASIEN NY. S (G1P0A0) DENGAN LOW BACK PAIN TRIMESTER III KEHAMILAN DI WILAYAH KERJA PUSKESMAS BOJONGSARI KECAMATAN BOJONGSARI - Nursefa Gusti Ayu (2023)
: Pregnancy is a period of life associated with changes in anatomy, physiology, psychological adaptation, and social environment. Changes and adjustments that occur during pregnancy commonly cause discomfort in pregnant women. Symptoms usually appear during pregnancy, with the most common symptoms appearing in the third trimester of pregnancy. Back pain is one of the most common third trimester symptoms. Low back pain is a common condition especially in late pregnancy when the center of gravity shifts. One attempt to relieve back pain during pregnancy is exercise during pregnancy. Method: This case research design uses a simple descriptive method in the form of a case study in implementing nursing care for Mrs. F (G1P0A0) with low back pain problems in the third trimester of pregnancy in the Bojongsari Lama environment, Bojongsari District on March 27, 2023. Data collection was carried out through home visits, interviews, observations, physical examinations, and documentation. Results: The main nursing diagnosis is acute pain associated with physiological agents of injury, pain scale measurement with a numeric rating scale/NRS. The main nursing action is pregnancy exercise to treat back pain. Conclusion: Low back pain can be reduced as indicated by the results of measurements using the numeric rating scale/NRS which decrease gradually after nursing actions are carried out and evaluation is carried out with SOAP documentation.